Meta analysis in online journalism - Nurutdinova Madinabonu Chorievna; Dildora Rizaeva (International Journal of Technology and Education Research, 2023)
This article is about a destructive analysis system in online journalism. The types of meta-analysis are classified according to their origin and internal structure. About the use of meta-analysis in content composition and classification in different formats. A meta-analysis involves a systematic review, identification of evidence, and critical evaluation of research or specific research. From the point of view of objectivity, reliance on the criterion of accuracy is important in all accounting books